Comparative Analysis of Life Cycle Carbon Emissions Between Copper and Aluminum Core Power Cables in Low-Voltage Distribution Networks - Yang Sirui; Zhang Yanchi (E3S Web of Conferences)
Accurate carbon footprint assessment of low-voltage distribution network components is critical for achieving carbon neutrality. This study conducts a comparative life cycle assessment (LCA) of copper- core (YJV) and aluminum-core (YJLV) power cables, covering raw material extraction, manufacturing, transportation, operation, and end-of-life stages. A quantitative LCA model is established to evaluate emissions under equivalent current-carrying capacity. A case study based on typical cable specifications shows that, due to aluminum’s higher carbon footprint factor compared to copper, aluminum-core cables have higher emissions during manufacturing. However, aluminum offers greater recycling potential, and increasing the share of recycled aluminum can significantly reduce its carbon footprint. Due to higher electrical resistance, aluminum-core cables also result in significantly higher operational emissions compared to copper- core cables. The findings reveal that conductor selection leads to distinct emission profiles across life-cycle stages and must be evaluated comprehensively, considering service life, power generation mix, and load characteristics. This study provides theoretical support and practical guidance for low-carbon cable selection and emission optimization in distribution networks.